2020
DOI: 10.1177/0391398820910751
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygenation improvement is associated with hemoglobin increase after hemodialysis initiation

Abstract: Introduction: Near-infrared spectroscopy has been used to measure the regional oxygen saturation (rSO2) of the brain, and decreases in cerebral rSO2 have been reported to lead to cognitive impairment in patients undergoing hemodialysis. However, reports about the association between changes in cerebral oxygenation and clinical parameters at hemodialysis initiation, including hemoglobin level, are lacking. Methods: This study included 33 patients at the hemodialysis initiation phase. Cerebral rSO2 was monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The first found that HD patients with cognitive impairment had lower rSO 2 levels in the brain than patients with normal cognitive functions [67]. The second study found that changes in rSO 2 levels in the brain are significantly related to hemoglobin levels, pulse rate, and serum albumin levels [68].…”
Section: Fluctuations In Cerebral Blood Flow and Cognitive Functionmentioning
confidence: 99%
“…The first found that HD patients with cognitive impairment had lower rSO 2 levels in the brain than patients with normal cognitive functions [67]. The second study found that changes in rSO 2 levels in the brain are significantly related to hemoglobin levels, pulse rate, and serum albumin levels [68].…”
Section: Fluctuations In Cerebral Blood Flow and Cognitive Functionmentioning
confidence: 99%
“…Results of near-infrared spectroscopy studies, which evaluate the regional oxygen saturation (rSO2) of the brain revealed contradictory results. Ito et al 20 demonstrated an increase in follow-up cerebral rSO2 values compared with the values at the beginning of HD, which may be due to an improvement in hemoglobin levels after dialysis. Another cohort of 15 pediatric patients receiving chronic HD identified no significant difference between pre and post-HD values of cerebral rSO2 21 .…”
Section: Discussionmentioning
confidence: 95%
“…Low tissue oxygenation may have negative influence on HD patients. Anemic conditions, overhydrated status, and hypotension could induce organ hypoxia in the brain or intra-abdominal organs [20][21][22][26][27][28] . Furthermore, cerebral oxygenation impairment could be related to cognitive impairment 29,30 , and access hand rSO 2 was reportedly associated with grip strength 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, each rSO 2 measurement was performed at rest in the supine position in the bed for at least 5 min, and mean values were defined as the measured rSO 2 values. The attachment parts of the sensor and monitoring time of rSO 2 were determined based on previous reports 10 , 12 , 19 , 27 . Measured rSO 2 values were shown as results before and after PTA.…”
Section: Methodsmentioning
confidence: 99%